Empowering Families as Primary Educators in Building Character Foundations in Early Childhood - Muhammad Nurfazri; Sri Mellia Marinda; Ferli Septi Irwansyah (UIN Sunan Gunung Djati Bandung, 2024)
Character development is one of the pivotal factors in determining a nation's progress, with the quality of its generation playing a crucial role. Thus, cultivating and nurturing strong character from early childhood is essential. Early childhood represents a critical period for shaping foundational thought processes and behaviours, vital components of an individual's personality. Hence, education should prioritize character and personality formation and begin with family. This literature review explores the role of families as primary educators in building character foundations in early childhood based on Islamic values. As the smallest social unit and the first educational institution in a child's life, the family plays a central role. To effectively educate and shape a child's character, families must consider the critical factors of mindset and attitude patterns. The mindset is a primary reference in perceiving various matters, while attitude patterns connect physical needs and instincts to these mindsets. In addition, families should address other essential elements such as religious knowledge, psychology, philosophy, social interactions, and moral education to support a child's character development fully. Moreover, Islam provides comprehensive guidance on meeting these needs, positioning the family as the child's primary motivator. While this study offers valuable insights, it acknowledges certain limitations and encourages further research to expand the understanding of character education and its implementation within an Islamic context.